Papers on Quintilian and ancient declamation - Winterbottom, Michael, 1934- (Oxford University Press, 2019)
Declamation--the practice of training young men to speak in public by setting them to compose and deliver speeches on fictional legal cases--was central to the Greek and Roman educational systems over many centuries and has been the subject of a recent explosion of scholarly interest. This book brings together a broad selection of scholarly work published since 1964. The papers and reviews focus on two related topics: the rhetorician Quintilian and ancient declamation in general. Quintilian, who taught rhetoric at Rome in the second half of the first century ad, was the author of the Institutio oratoria, a key text for Roman educational practice, rhetoric, and literary criticism. Subjects explored here range widely; they cover not only the establishment and interpretation of the text and its literary and historical context, but also Quintilian's views on inspiration, morality, philosophy, and declamation, of which he was a practitioner. While the volume also offers detailed examinations of the texts and interpretations of a wide range of Latin and Greek authors, such as Seneca the Elder, Sopatros, and Ennodius, there is a particular focus on two collections wrongly attributed to Quintilian, the so-called Minor and Major Declamations. A previously unpublished re-assessment of the manuscript tradition of the latter collection is included here.